2009
DOI: 10.1002/adsc.200900325
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis Esterase (BS2) and its Double Mutant Have Different Selectivity in the Removal of Carboxyl Protecting Groups

Abstract: An esterase from Bacillus subtilis (BS2) and its double mutant E188W/M193C quickly hydrolyze n-butyl, n-propyl, methoxyethyl and allyl esters. The wild-type BS2 preferentially removes such esters from the g-position of glutamate diesters, while the engineered enzyme has a reversed selectivity removing esters from the a-position of glutamate diesters.Automated docking and molecular dynamic simulations were performed to understand the molecular reason for the different regioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…13 Moreover, enzymes have proven their effectiveness in the selective modification of a wide range of functionalities, mainly using hydrolytic or redox enzymes. For instance, acylases, esterases, lipases and proteases are recognized as efficient enzymes for the deprotection of alkyl esters including benzylic ones, [14][15][16][17][18] amides 19 and carbamates. 20 Also, oxidoreductases have shown the potential to carry out N-deprotection reactions.…”
mentioning
confidence: 99%
“…13 Moreover, enzymes have proven their effectiveness in the selective modification of a wide range of functionalities, mainly using hydrolytic or redox enzymes. For instance, acylases, esterases, lipases and proteases are recognized as efficient enzymes for the deprotection of alkyl esters including benzylic ones, [14][15][16][17][18] amides 19 and carbamates. 20 Also, oxidoreductases have shown the potential to carry out N-deprotection reactions.…”
mentioning
confidence: 99%
“…The variant has a clear preference for the regioselective hydrolysis at the R-position of glutamate diesters, while the wild-type BS2 preferably cleaves the γ-ester. 167 The hydrolysis rate of 7-aminocephalosporanic acid to the 3-desacetyl derivative (HACA) was improved by a factor of 4 when B. subtilis MTCC 121 esterase was mutated to variants R231G, Y222H/D43G, and M138V. 168 Directed evolution was performed to improve the properties of enzyme LovD toward the semisynthesis of simvastatin from monacolin J acid (MJA) and a synthetic R-dimethylbutyryl thioester.…”
Section: Transferases Ec2mentioning
confidence: 99%
“…Variant E188W/M193C of esterase BS2 shows an altered selectivity in the hydrolysis reaction of various ( Z )-glutamate diesters. The variant has a clear preference for the regioselective hydrolysis at the α-position of glutamate diesters, while the wild-type BS2 preferably cleaves the γ-ester …”
Section: Examples Of Designed Enzymes For Applications In Organic Syn...mentioning
confidence: 99%
“…Engineering of the esterase BS2 from Bacillus subtilis had a marked effect on the regioselectivity of ester hydrolysis in the transformation of glutamate diesters protected at both the aand g-positions. 19 The wild-type enzyme hydrolysed substrate 18 to give only the a-deprotected carboxylic acid 19, yet, the Glu188Trp/Met193Cys mutant gave a ratio of 1 : 2 for the aand g-deprotected products 19 and 20 respectively (Scheme 4). In a more extreme example of esterase engineering, Kaslauskas and Bornscheuer showed that the esterase from Pseudomonas fluorescens can be converted into an epoxide hydrolase.…”
Section: Esterasesmentioning
confidence: 99%